Pelatihan Five Finger Therapy dalam Meningkatkan Kualitas Tidur Warga Binaan Pemasyarakatan - Suhariyanti, Enik; Rohita, Tita; Hertini , Reni; Rohimah, Siti (Yayasan Inspirasi El Burhani, 2024)
Introduction: Inmates (hereinafter referred to as WBP) often experience mental health disorders including depression, severe stress, and anxiety. This affects the quality of sleep which will trigger other health problems such as heart failure, coronary heart disease, and heart attacks. Objective: to socialize and train five-finger therapy or hereinafter referred to as Five Finger Therapy in improving sleep quality in Inmates (WBP). Method: th method of this activity uses lectures in socialization and training simulations. The number of participants is 40 people. The activity starts from the preparation, implementation, and evaluation stages. Data was collected through surveys, interviews, and observations before and after the implementation of therapy. Result: the results of the activity showed that out of 40 respondents to WBP in the Class 2B Banjar City male prison, it was found that before Five Finger Therapy was carried out, 30 WBP experienced poor sleep quality (75.0%) and 10 people or 25% had good sleep quality. After Five Finger Therapy was carried out, the category of good sleep quality increased to 32 people (80.0%) and poor quality decreased to 18 people (20.0%). Conclusion: this indicates that Five Finger Therapy has successfully improved the quality of WBP sleep, so that the training is effective in improving the quality of sleep of male WBP in prison. This therapy makes a positive contribution to the mental health of WBP. Recommendations for the continued implementation of five finger therapy and the importance of support from friends and prison officers in facilitating the action